Effectiveness of Dynamic Neuromuscular Stabilization Technique in Neurological Conditions: An Updated Review - Kaushik, Himani; Choudhary, Avi; Sharma, Mitushi (Journal of Health and Allied Sciences NU, 2024)
Objective This updated review aims to identify the effectiveness of dynamic neuromuscular stabilization (DNS) techniques in neurological conditions.Method A literature search was carried out from 2013 to 2024 on PubMed, Google Scholar, Research Gate, and Scopus databases. Following keywords were used to identify the relevant articles such as dynamic neuromuscular stabilization, reflex-mediated DNS, neurological conditions, DNS, cerebral palsy, stroke, Parkinson's disease, multiple sclerosis, neurodegenerative conditions, ataxia, Alzheimer's disease, and multiple sclerosis with Boolean operators. All the full-text, English-written articles based on inclusion and exclusion criteria were included in the review irrespective of their experiment study design, only the review article was excluded.Results This updated review included 10 articles related to neurological conditions including, stroke, multiple sclerosis, Alzheimer's disease, Parkinson's disease, and cerebral palsy. The results show significant differences in various outcome measures of the included studies.Conclusion The findings suggest that DNS is an effective approach to use in the rehabilitation protocol of neurologically impaired patients and is beneficial in improving their health outcomes and overall quality of life. This review concludes that more evidence is required in this area of research with good quality research and long follow-up periods.
Keywords: DNS; rehabilitation; neurological conditions; dynamic neuromuscular stabilization; quality of life